Credentials: Breast Slang and the Discourse of Femininity - Naugler, Diane (Atlantis, 2009)
This article situates a thematic discourse analysis of accumulated breast slang within the representational production of ideal female breasts in the service of normative femininity. These ideals also participate in a number of interrelated discourses including race and gender relations.